Cost-Effectiveness of Intensive Tobacco Dependence Intervention Based on Self-Determination Theory - Pesis-Katz, Irena (2011)
OBJECTIVES: To evaluate cost-effectiveness of a tobacco dependence intervention based on self-determination theory (SDT) and consistent with the Public Health Service (PHS)-sponsored Clinical Practice Guideline for Treating Tobacco Use and Dependence. STUDY DESIGN: Adult smokers were recruited into a randomized cessation-induction trial of an intensive intervention versus community care. Seven-day point prevalence (7dPP) tobacco abstinence and cost-effectiveness of the intervention were examined using 737 participants with health insurance. METHODS: Community care (CC) participants received smoking-cessation pamphlets and information on local treatment programs. Intervention participants received those materials and were asked to meet 4 times over 6 months with study counselors to discuss their health in a manner that supported autonomy and perceived competence. The third-party payer’s perspective was used for this analysis, and the primary outcome was cost-effectiveness using self-reported 7dPP tobacco abstinence at 6 months. Sensitivity analyses were performed using costs of generic medications, biochemically validated tobacco abstinence, actual rates of tobacco abstinence, life-years saved (not adjusted for quality of life), and costs in 2011 US dollars. A subgroup analysis was conducted using smokers who did not want to stop within 30 days. RESULTS: Smokers in the intervention, relative to CC, were more likely to attain 7dPP tobacco abstinence at 6 months. The overall incremental cost-effectiveness ratio was $1258 per quality-adjusted life-year saved, in US dollars. The sensitivity and subgroup analyses yielded similar results. CONCLUSIONS: An intervention based on SDT and consistent with the PHS Guideline facilitated tobacco abstinence among insured smokers and was cost-effective compared with other tobacco dependence and medical interventions.